Herencia de la necrosis marrón y de otros caracteres del trigo en el Perú - Villanueva Novoa, R. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The inheritance of several characters was studied in a cross between the wheat varieties ´Rew-H44-Rhod´, low yielding and brown necrosis susceptible, and ´Nariño 59´, good yielding and brown necrosis resistant. The studies were made in three widely apart localities in Peru. Inheritance of qualitative morphological characters, such awn length, spike color, and grain color, took place in simple mendelian form. There were differences, according to locality, in the inheritance of quantitative characters, such as grain number and weight per spike, protein content and quality (Pelshenke index), resistance to brown necrosis, and tillering concordance. Tests indicate that there are three pairs of genes for inheritance of tillering, spike grain number and weight, and protein content. There was no tendency to association between almost any pair of the characters studied.